2017
DOI: 10.1016/j.ebiom.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neopterin Levels Predict Early Death in Older Hip-fracture Patients

Abstract: Our society faces a major challenge concerning management of the health and socio-economic burden caused by acute physical stress in the older population (+ 75 years). In particular, hip-fracture surgery (HFS) represents a major health care preoccupation, affecting 1.6 million patients worldwide, resulting in a significant drop in life quality and autonomy. The trauma is associated with 20–30% one-year mortality in the elderly. In the present study, we aim to identify factors, which influence and/or predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
2
6
0
1
Order By: Relevance
“…Patients with HF were 87 years old [83-92] and 27% were men. As expected, patients exhibit characteristics of geriatric population: they were comorbid (the median CIRS = 9 [7][8][9][10][11][12][13], polymedicated for 63% of them,…”
Section: Patients Characteristicssupporting
confidence: 72%
See 1 more Smart Citation
“…Patients with HF were 87 years old [83-92] and 27% were men. As expected, patients exhibit characteristics of geriatric population: they were comorbid (the median CIRS = 9 [7][8][9][10][11][12][13], polymedicated for 63% of them,…”
Section: Patients Characteristicssupporting
confidence: 72%
“…Finally, HF prognosis has been associated with an increase of pro-inflammatory cytokines (IL-6, TNF-α) and few biomarkers have been described (c-reactive protein, procalcitonin) ( 7 , 12 ). In a previous study, we observed that pre-operative rate of neopterin (a molecule secreted by myeloid lineage under IFN-γ stimulation) was strongly associated with long-term mortality ( 13 ). The objective of this longitudinal study is to decipher immune changes occurring in the 1st days following HF and determine how phenotype, function, and regulation of innate and adaptive compartments adapt during acute stress event.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neopterin is thought to have a correlation with ROS production so that it can be an indicator of oxidative stress as a trigger for the progres-sion of HIV disease to become more severe as the number of CD4+ T-lymphocyte cells de-creases. 19 This study shows the results of the analysis of a significant difference in serum neopterin levels in the living group and the deceased group (p=0.041). While the correlation analysis between serum neopterin levels and CD4+ cell counts showed no significant correlation (p=0,132).…”
Section: Discussionmentioning
confidence: 63%
“…Une publication récente a montré que les taux plasmatiques de néoptérine, une molécule produite par les macrophages et les monocytes sous l'influence de l'IFN-γ, sont prédictifs de mortalité à un an d'une FESF chez les personnes âgées. De plus, la néoptérine, mesurée à l'arrivée à l'hôpital, est corrélée négativement au temps de survie après la chirurgie [49]. Il est intéressant de noter que la voie conduisant à la production de néoptérine est couramment utilisée pour la synthèse de la 5,6,7,8-tétrahydrobioptérine (BH4), essentielle à la synthèse de la dopamine et de la sérotonine, deux hormones impliquées dans les réponses au stress.…”
Section: Fracture De L'extrémité Supérieure Du Fémur (Fesf)unclassified